2015
DOI: 10.1063/1.4932633
|View full text |Cite
|
Sign up to set email alerts
|

Tetra-methyl substituted copper (II) phthalocyanine as a hole injection enhancer in organic light-emitting diodes

Abstract: We have enhanced hole injection and lifetime in organic light-emitting diodes (OLEDs) by incorporating the isomeric metal phthalocyanine, CuMePc, as a hole injection enhancer. The OLED devices containing CuMePc as a hole injection layer (HIL) exhibited higher luminous efficiency and operational lifetime than those using a CuPc layer and without a HIL. The effect of CuMePc thickness on device performance was investigated. Atomic force microscope (AFM) studies revealed that the thin films were smooth and uniform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Phthalocyanines (Pcs) are planar macrocyclic compounds with extended 18 π-electron conjugated system that display unique electronic and optical properties. Because of their fascinating properties as well as their thermal and chemical stability, Pcs were intensively studied as prospective compounds for photodynamic therapy (PDT) of cancer, near-IR imaging agents, organic-based solar cells, and organic light-emitting diodes (OLEDs). The aggregation behavior exhibited by the large and planar Pc macrocycles results in a drastic change of their optical properties, thus limiting their use in many applications. For example, such undesired behavior can greatly affect the PDT activity and nonlinear optical properties by reducing the active absorbing excited-state lifetime. , Therefore, the large architectural flexibility characterized by the Pc structure can be exploited to tune the molecular properties in pursuit of optimized optical features (color, aggregation, optical absorption, etc.) for the required applications.…”
Section: Introductionmentioning
confidence: 99%
“…Phthalocyanines (Pcs) are planar macrocyclic compounds with extended 18 π-electron conjugated system that display unique electronic and optical properties. Because of their fascinating properties as well as their thermal and chemical stability, Pcs were intensively studied as prospective compounds for photodynamic therapy (PDT) of cancer, near-IR imaging agents, organic-based solar cells, and organic light-emitting diodes (OLEDs). The aggregation behavior exhibited by the large and planar Pc macrocycles results in a drastic change of their optical properties, thus limiting their use in many applications. For example, such undesired behavior can greatly affect the PDT activity and nonlinear optical properties by reducing the active absorbing excited-state lifetime. , Therefore, the large architectural flexibility characterized by the Pc structure can be exploited to tune the molecular properties in pursuit of optimized optical features (color, aggregation, optical absorption, etc.) for the required applications.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Since the first demonstration of the use of copper phthalocyanine (CuPc) to modify the ITO anode of an OLED by Tang and VanSlyke in 1996, [5] the use of metal phthalocyanines (MPcs) as anode buffer layers has been subject to intensive investigation with the aim of achieving higher OLED efficiencies and stabilities. [5,9,10,[25][26][27][28][29][30] In most cases, these MPc layers are fabricated via the vacuum sublimation method because of the poor solubility of typical MPcs in organic solvents. [5,25,30] While vacuum processing eases the fabrication of complex OLED configurations with the desired performance and high reliability on a laboratory scale, this approach is very costly because of the expense of maintaining an ultrahigh vacuum combined with its high energy consumption, high operating temperatures, and huge materials losses.…”
Section: Introductionmentioning
confidence: 99%
“…Akanksha Uniyal and Poornima Mittal [23] provide a comparison of the bilayer and multilayer OLED. Yu-Long Wang et al [24] used tetramethyl substituted copper (II) phthalocyanine as a hole-injection enhancer in OLED. More recently, Xu et al [25] developed a multilayer transparent conducting electrodes for OLEDs, while Meiling Shan et al [26] reported an enhanced hole injection in OLEDs utilizing a copper iodidedoped hole-injection layer.…”
Section: Introductionmentioning
confidence: 99%